Joint Sub-Committee of the T.U.C., the Labour Party and the Co-operative Congress on the Government White Paper "A National Health Service" (minutes) - Labour Party (Great Britain) ; Co-operative Congress
1944-09-05 1944 1940s 6 pages -6- on these matters with interests involved. There must be proper democratic control of the whole scheme and the Minister concerned should be responsible in answering for it in Parliament. 11. APPLIANCES (Medical, Surgical, Dental, Optical) The provision of appliances is essential for restoration, or maintenance of health and for rehabilitation. The White Paper invites consideration as to whether patients should be called upon to contribute towards the cost of more expensive appliances, or at least of repairs and replacements. We are of opinion that no part of the initial cost of such items should fall on patients, although there should be suitable safeguards in connection with renewals or repairs. 12. DRUGS It is of course very necessary that patients should be able to obtain prescribed medicines with a minimum of inconvenience and in the most efficient and economical way. We suggest therefore that the media for the supply of medicine should be the existing panels of retail pharmacy as well as hospitals and the local health centres. We do not, however, think that medicine should be provided at the doctor's surgery except in an emergency. In all circumstances, the primary consideration must be the supply of medicine to meet adequately the needs of the public. JLS/EM/1129/21.9. 292/847/2/10